Cerebral Ischemic Postconditioning Plays a Neuroprotective Role through Regulation of Central and Peripheral Glutamate. (19th July 2018) - You, Jiulin; Feng, Liangshu; Xin, Meiying; Ma, Di; Feng, Jiachun
Abstract : Following cerebral ischemia/reperfusion (I/R) injury, a series of pathophysiological processes are stimulated in both the central nervous system (CNS) and the periphery, including, but not limited to, the peripheral immune and endocrine systems and underregulation of the neuroendocrine-immune network. Glutamate (Glu) is an important excitatory neurotransmitter in the CNS; its excitotoxicity following cerebral ischemia has been a focus of study for several decades. In addition, as a novel immunoregulator, Glu also regulates immune activity in both the CNS and periphery and may connect the CNS and periphery through regulation of the neuroendocrine-immune network. Ischemic postconditioning (IPostC) is powerful and activates various endogenous neuroprotective mechanisms following cerebral I/R, but only a few studies have focused on the mechanisms associated with Glu to date. Given that Glu plays an important and complex pathophysiological role, the understanding of Glu-related mechanisms of IPostC is an interesting area of research, which we review here.